Relationship between endogenous hormone levels of grapevine callus cultures and their morphogenetic behaviour - Jiménez García, Víctor (2000)
Dark callus cultures from leaves and anthers of three grapevine genotypes (Seyval blanc, Riesling and Trollinger) were propagated in vitro for almost two years on medium deprived of growth regulators. Three different callus lines originated from these initial callus cultures: A dark non-embryogenic one, another composed by clusters of somatic embryos and a friable, whitish callus line that can produce somatic embryos under appropriate circumstances, Endogenous hormone levels viz, indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins A1, A3 and A20, zeatin/zeatin riboside and N6(∆2-isopentenyl) adenine/ N6(∆2-isopentenyl) adenosine, were analysed in the different callus types. Only higher ABA levels correlated with the morphogenetic capacity of the cultures. When endogenous hormone levels were analysed in the line constituted by conglomerates of somatic embryos at different dates during the whole culture period, higher levels of IAA and ABA were found during the winter months even if the cultures were maintained permanently under constant temperature and photoperiod conditions. A 4-week chilling period led to a reduction of the endogenous ABA level.